Factores de riesgo y su incidencia en el desarrollo del asma bronquial en los niños de 2 a 12 años Ciudadela Primero de Diciembre de Babahoyo octubre 2018 - abril 2019 - Zarate Acosta, Angel Leonardo (2019)
Bronchial asthma is considered as a chronic disease, which affects the bronchi and involves people regardless of age and sex but mostly to children between 5 and 10% of the child population; sometimes this can be severe and in the end of the mortal cases. It is a disease that is considered a global health problem. Identify and keep track of risk factors. The general objective of this research was to determine the risk factors in children from 2 to 12 years of age in the citadel first of December. The same one that had its development through the quantitative modality, whose type of research is cross-sectional descriptive and taking as sample in study 45 children aged 2-12 years who suffer from asthma, the same ones that were represented by their parents at the time in which the surveys were carried out to obtain the necessary information in this study, in which it was found that environmental risk factors are those that affect the development of bronchial asthma, having as conclusion that in the citadel first of December, the knowledge they have about bronchial asthma is very primitive, with the result that in females and 7-9 years old it is the most frequent in which respiratory therapy was performed in the home for the control of the disease.